Pendistribusian Dana Zis (Zakat Infaq Dan Shadaqah) Dalam Mengoptimalkan Personal Branding UMKM Di Kecamatan Kalibaru (Studi Kasus Di Lazismu Kecamatan Kalibaru) - muhammad syafi'i; Feby Diah Vita Hifaturrisqi (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
The obligation of Muslims to improve the economy of their people is through zakat, infaq, and alms. The amil zakat institution has a mandate as a facilitator in the process of collecting, managing, and distributing ZIS funds (zakat infaq and sadaqah). The main economic sector, MSMEs, is a stand-alone business sector with limitations in business branding. The purpose of this study is to describe the collection, management, and distribution of ZIS funds (zakat infaq and sadaqah) by LAZISMU Kalibaru in optimizing the personal branding of SMEs in the Kalibaru District. This research method uses the descriptive qualitative method. The results and conclusions of this study are in the process of collecting ZIS funds (zakat infaq and sadaqah) at LAZISMU Kalibaru in two ways, direct and indirect. The management of ZIS funds (zakat infaq and sadaqah) is intended to improve the welfare of the social life of the community by establishing 10 programs which are divided into two areas, namely social and health. The distribution of ZIS funds in the social sector, including to MSMEs through a branding program in the form of painting and design either in places or business carts, in the LAZISMU Kalibaru branding program has compared 4 MSMEs with businesses in the culinary field. The purpose of this branding program is as a form of concern for LAZISMU Kalibaru in improving and developing the MSMEs' businesses in the Kalibaru sub-district.